Educational Inspectorate and Internationalisation: A Critical Reflection from an Erasmus+ KA1 Mobility Experience - Pérez de Tudela Delgado, Ana (Avances en Supervisión Educativa, 2026)
This article analyzes the first institutional internationalization initiative of the Andalusian Education Inspectorate, which materialized in an Erasmus+ KA1 mobility program held in Padua, Italy, in October 2025, within the framework of strategic objective OE5.3 of the Andalusian Education Inspectorate’s General Action Plan 2023-2027. The article combines a reflective analysis of this mobility program with a narrative review of the specialized literature on inspection and internationalization, subsequently identifying the lessons learned. These lessons are identified in the areas of conflict resolution, the structural limitations of mobility—especially the added workload—and the difficulties of transferring knowledge between educational systems with different traditions. It concludes by formulating concrete proposals for the Andalusian and national education administrations aimed at guaranteeing the continuity and institutionalization of the European dimension of the inspectorate’s role.